Clinical manifestation and laboratory findings in positive blood culture in neonatal septicemia - Gholamreza Khademi; Ahmad Shah Farhat; Ashraf Mohammadzadeh (Mashhad University of Medical Sciences, 2014)
Background/objective: Neonatal septicemia is one of the major causes of mortality in newborns. The aim of this study is to evaluate the clinical manifestations and laboratory findings in positive blood culture in neonatal septicemia. Methods: In this retrospective study, we allocated 100 records positive blood culture of neonates suffering from septicemia. A questionnaire was completed for each patient consisting the age at admission, gender, weight at birth, admission time, type of delivery, pre- or post-term delivery and the clinical symptoms. Types of organism causing sepsis, and their resistance to antibiotics were evaluated and method for empirical treatment was recommended. Results: Respiratory distress, cyanosis and lethargy were more common in the patients. The antibiogram showed Ampicillin resistance in 86% and Gentamycin resistance in 66% of studied records. Also, 36% cases of positive blood culture with gram-negative and 64% with gram-positive bacteria were observed. The most common bacteria in blood cultures were negative-coagulase Staphylococcus (%35), Staphylococcus Aureus (%24), Klebsiella (%18), respectively. Other bacteria were Enterobacter, Escherichia coli and Enterococcus (%5), Acinetobacter (%3), Pseudomonas aeruginosa and Negative-Gram Bacilli (%2) and Ceratia (%1). The most common effective antibiotics against bacterial growth in Antibiograms were Vancomycin, Cephalosporin, Amikacin, Co-trimoxazole and Gentamycin. Conclusion: Since the most common bacteria in neonatal septicemia cases were negative-coagulase Staphylococcus, Staphylococcus Aureus, Klebsiella, the pediatricians must select the regiments that cover gram-negative bacteria for empirical antibiotic treatments.